1993
DOI: 10.3354/cr002215
|View full text |Cite
|
Sign up to set email alerts
|

Climatic changes and trends over a major river basin in India

Abstract: ABSTRACT. Long-term changes of seasonal and annual surface air temperatures and precipitation of the Mahanadi river basin in India are presented. The long-term trends in these 2 important climatic elements were evaluated by linear trend analysis. The results indicate that there is a highly significant warming trend in the mean maximum, mean minimum and average mean temperatures of the basin based on data from 7 stations for the period 1901-80. Results of the trend analysis of surface air temperatures of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 3 publications
5
23
0
Order By: Relevance
“…Much research has been undertaken using the Mann-Kendall test to detect trends in climatological and hydrological time series (e.g. Rao, 1993;Kothyari and Singh, 1996;Brunetti et al, 2000;Yue and Hashino, 2003;Abdul and Burn, 2006;Jiang et al, 2007;Modarres and Silva, 2007), and this particular non-parametric test has been shown to be more powerful than some parametric tests when dealing with skewed data (Önöz and Bayazit, 2003).…”
Section: Trends In Hydrological Extremesmentioning
confidence: 99%
“…Much research has been undertaken using the Mann-Kendall test to detect trends in climatological and hydrological time series (e.g. Rao, 1993;Kothyari and Singh, 1996;Brunetti et al, 2000;Yue and Hashino, 2003;Abdul and Burn, 2006;Jiang et al, 2007;Modarres and Silva, 2007), and this particular non-parametric test has been shown to be more powerful than some parametric tests when dealing with skewed data (Önöz and Bayazit, 2003).…”
Section: Trends In Hydrological Extremesmentioning
confidence: 99%
“…They also describe a decline in the number of cold days and increase in the number of extremely hot days. A fine study is performed by Rao (1993) where he chalked out significant warming trend in minimum, maximum and mean temperatures at Mahanadi river basin, India. It has also been reported that in future the temperature will rise by several degrees along with increased precipitation (Singh, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Highly significant warming trend in the mean maximum, mean minimum and average mean temperatures of the Mahanadi river basin was reported by Rao (1993) in seven stations between 1901 and 1980. Increased maximum temperature and trendless minimum temperature, resulting in the rise in mean and diurnal range of temperature trend analyses, was reported by Rupakumar and Krishankumar (1994) for maximum and minimum temperature data derived at 121 stations in India during 1901-1987.…”
Section: Resultsmentioning
confidence: 99%